Staten: sociologiska perspektiv (Sociologisk Forskning, 1997)
The State: sociological perspectivesThis article reviews and discusses new sociological works on the Swedish state. The state (with the exception of the welfare state) was nearly absent in Swedish sociology until the beginning of the 1980's. Since that time several works, produced mainly by researchers of the third generation in Swedish sociology, have been published. These works are products of three distinct developments: the international debate about the role of the capitalist state, the critique of the quantitative approaches in Swedish sociology and the insights concerning the limits of the modern state. The new studies are characterized by theoretical eclecticism and methodological pluralism. This article is mainly focused on the theoretical and methodological traditions and issues and ends with suggestions on how new research questions could be formulated.